Kompetensi Literasi Informasi Topik Kesehatan Mental Generasi Z di Era Digital (Studi Kasus Mahasiswa FBS Universitas Negeri Padang) - Afriliana, Elsya; Primadesi, Yona (Lembaga Yasin AlSys, 2024)
This research aims to determine the information literacy competency of generation Z mental health topics in the Digital Era (Case Study of Padang State University FBS Students). Information literacy competency is measured using the seven pillars SCONUL information literacy model with indicators: identify, scope, plan, gather, eval_uate, manage, and present. This research method is quantitative descriptive. The population of this research is FBS students class of 2020 totaling 1,080 population. The sample in this study amounted to 91 samples using the Slovin formula and the technique used was proportional random sampling. Data collection in this study used multiple choice test questions. Based on the research results, it is known that: (1) ability regarding identify is in the medium category with an average of 57.6; (2) ability regarding scope is in the medium category with an average of 56.7; (3) ability regarding plans is in the good category with an average of 61.9; (4) the ability to gather is in the medium category with an average of 58; (5) the ability to eval_uate is in the good category with an average of 67.7; (6) the ability to manage is in the good category with an average of 63; (7) ability regarding the present is in the good category with an average of 62.8. Overall the indicator obtained an average of 61.1 in the good category, this shows that students have information literacy skills on mental health topics.